Perplexing Metamorphoses of the Demarcation Problem. - Vecsey, Zoltán (Theoria: A Swedish Journal of Philosophy, 2025)
In their recent paper in Theoria, Hirvonen and Karisto present an analysis of the differences between traditional and contemporary approaches to the demarcation problem. They put forward a diagnosis according to which the traditional approaches depend on six assumptions regarding the nature of the problem. In their view, all of these assumptions may be regarded as unnecessary. They conclude that the traditional approaches can be discarded without thereby giving up on the demarcation problem. I shall argue that, although Hirvonen and Karisto's diagnosis is helpful in certain respects, their conclusion may be questioned.